Iron-Catalyzed Reductive Metalation–Allylation and Metalative Cyclization of 2,3-Disubstituted Oxetanes and Their Stereoselectivity - Sugiyama, Yu-ki; Heigozono, Shiori; Tamura, Kazuhiro; Okamoto, Sentaro (Synthesis, 2016)
A novel process for the reductive magnesiation of 2-substituted oxetanes and the metalative cyclization of ω-alkynyl oxetanes is developed using n-propylmagnesium chloride in the presence of an iron catalyst. The generated intermediate organomagnesium compounds react with electrophiles. The reactions of 2,3-disubstituted oxetanes and their subsequent allylation with allyl halides in the presence or absence of copper(I) cyanide as the catalyst is studied with a unique switching of stereoselectivity being observed in the absence or presence of copper(I) cyanide . In addition, it is found that the metalative cyclization of 3-substituted 2-alkynyl oxetanes proceeds in an anti-selective manner starting from both syn- and anti-substrates. In all cases, the stereochemistry at the 2-position of the oxetanes is lost during the reactions suggesting the involvement of a radical process.
Keywords: iron catalyst; oxetanes; reductive magnesiation; metalative cyclization; (3-oxidopropyl)magnesium; diastereoselective reaction